Nuclear Import of a Secreted “Candidatus Liberibacter asiaticus” Protein is Temperature Dependent and Contributes to Pathogenicity in Nicotiana benthamiana - Liu, Xuelu; Fan, Yanyan; Zhang, Chao; Dai, Meixue; Wang, Xuefeng; Li, Weimin (Frontiers in Microbiology, 2019)
“Candidatus Liberibacter asiaticus” (CLas), one of the causal agents of citrus Huanglongbing (HLB), secretes proteins with functions that are largely unknown. In this study, we demonstrated that CLIBASIA_00460, one of the CLas-encoded Sec-dependent presecretory proteins, might contribute to the phytopathogenicity of CLas. CLIBASIA_00460 was conserved in CLas strains and expressed at a significantly higher level in citrus than in Asian citrus psyllid. Agrobacteria-mediated transient expression in Nicotiana benthamiana epidermal cells showed that the mature CLIBASIA_00460 (m460) without the putative Sec-dependent signal peptide was localized in multiple cellular compartments including nucleus at 25°C, but that nuclear accumulation was greatly decreased as the temperature rose to 32°C. When overexpressed via a Potato virus X (PVX)-based expression vector in N. benthamiana, m460 induced no local symptoms, but tiny necrotic spots were scattered on the systemic leaves. However, NLS-m460, which contains the SV40 nuclear localization sequence (NLS) at the N-terminus to promote nuclear import of m460, caused chlorosis and necrosis in the local leaves and severe necrosis in the systemic leaves. Taken together, these data suggest that CLIBASIA_00460 represented a novel virulence factor of CLas, and that nuclear localization of this protein was temperature dependent and positively correlated with its pathogenicity in planta.